How flower colour signals allure bees and hummingbirds: a community-level test of the bee avoidance hypothesis - de Camargo, Maria Gabriela Gutierrez [UNESP]; Lunau, Klaus; Batalha, Marco Antônio; Brings, Sebastian; de Brito, Vinícius Lourenço Garcia; Morellato, Leonor Patrícia Cerdeira [UNESP] (Wiley, 2019)
Colour signals are the main floral trait for plant–pollinator communication. Owing to visual specificities, flower visitors exert different selective pressures on flower colour signals of plant communities. Although they evolved to attract pollinators, matching their visual sensitivity and colour preferences, floral signals may also evolve to avoid less efficient pollinators and antagonistic flower visitors. We evaluated evidence for the bee avoidance hypothesis in a Neotropical community pollinated mainly by bees and hummingbirds, the campo rupestre. We analysed flower reflectance spectra, compared colour variables of bee-pollinated flowers (bee-flowers; 244 species) and hummingbird-pollinated flowers (hummingbird-flowers; 39 species), and looked for evidence of bee sensorial exclusion in hummingbird-flowers. Flowers were equally contrasting for hummingbirds. Hummingbird-flowers were less conspicuous to bees, reflecting mainly long wavelengths and avoiding red-blind visitors. Bee-flowers reflected more short wavelengths, were more conspicuous to bees (higher contrasts and spectral purity) than hummingbird-flowers and displayed floral guides more frequently, favouring flower attractiveness, discrimination and handling by bees. Along with no phylogenetic signal, the differences in colour signal strategies between bee- and hummingbird-flowers are the first evidence of the bee avoidance hypothesis at a community level and reinforce the role of pollinators as a selective pressure driving flower colour diversity.
Keywords: campo rupestre; colour contrast; floral guides; grassland; marker points; pollen mimicry; pollination; savanna